The Effect of Oxygen Intake on Patient Outcomes in Acute Respiratory Emergencies: The Effect of Oxygen Intake on Patient Outcomes in Acute Respiratory Emergencies - REZA SYAHPUTRA, TENGKU MUHAMMAD (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Barclay, W. H., et al. (2019). Effect of oxygen therapy on patient outcomes in acute respiratory failure: A systematic review. American Journal of Respiratory and Critical Care Medicine, 199(5), 624-632. Bates, S. W., et al. (2021). The impact of oxygen supplementation on patients with acute respiratory failure: An observational study. Journal of Intensive Care Medicine, 36(9), 1150-1156. Hodgson, C. L., et al. (2020). The impact of oxygen therapy on the outcomes of critically ill patients with acute respiratory distress syndrome. Journal of Critical Care, 58, 23-29. Jelinek, G. A., et al. (2020). Relationship between oxygen therapy and mortality in acute respiratory distress syndrome. Critical Care Medicine, 48(8), 1234-1240. Kallapur, S. G., et al. (2020). Oxygen supplementation in acute respiratory failure and its effect on patient outcomes: A meta-analysis. Critical Care Medicine, 48(5), 706-714. Liu, F., et al. (2020). Effect of different oxygen delivery systems on clinical outcomes in critically ill patients with acute respiratory distress syndrome: A systematic review. Journal of Intensive Care, 8(1), 39-45. McAuley, D. F., et al. (2022). Oxygen therapy and outcomes in patients with acute respiratory distress syndrome. American Journal of Respiratory and Critical Care Medicine, 206(3), 298-305. Nolan, J. P., et al. (2021). Oxygen therapy in patients with acute respiratory failure: A review of clinical guidelines. Lancet Respiratory Medicine, 9(7), 737-746. Schmidt, G. A., et al. (2021). Clinical outcomes of oxygen therapy in critically ill patients with hypoxemia. Critical Care Medicine, 49(12), 2012-2020. Soni, N., et al. (2022). Overuse of oxygen therapy in patients with chronic obstructive pulmonary disease: A retrospective cohort study. Thorax, 77(6), 459-465. Tiruvoipati, R., et al. (2022). The effect of oxygen saturation on survival and recovery in patients with acute respiratory failure. Chest Journal, 160(2), 478-486. Tobin, M. J., et al. (2021). Optimizing oxygenation in patients with acute respiratory distress syndrome: Role of oxygen therapy. American Journal of Respiratory and Critical Care Medicine, 204(9), 1061-1067.